VIRTUAL LABORATORY’S EFFECTIVENESS ON GRADE 11 LEARNERS’ ACADEMIC PERFORMANCE TOWARDS LEARNING ACID-BASE REACTIONS - Sibinda, Nicholas; Kabunga, Nachiyunde; Goodwell, Kaulu (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2025)
This study investigated the effectiveness of virtual laboratories on Grade 11 learners’ academic performance in learning acid-base reactions. A titration model was developed using the Scratch programming platform to simulate neutralisation reactions and facilitate related calculations. Employing a mixed-methods approach, the study collected qualitative data through interviews and non-participant observations, while quantitative data were obtained via a Likert scale questionnaire and pre- and post-tests. The Solomon four-group design was adopted as part of a convergence triangulation model. A total of 408 learners from four secondary schools participated in the study. Qualitative data were analysed using thematic analysis and the Mann–Whitney U test, while quantitative data were analysed using the Friedman test. Thematic findings revealed that learners found the Scratch-based learning experience engaging and interactive, particularly due to its multisensory approach that incorporated both visual and auditory modalities. Post-test results indicated that learners in the Scratch-based group outperformed their peers who were taught using PowerPoint presentations. The findings suggest that virtual laboratories designed through Scratch can significantly enhance conceptual understanding and academic performance in acid-base chemistry.